NILAI MORAL DALAM NOVEL SAD GIRLS (DUSTA & KEPEDIHAN) KARYA LANG LEAV - Una Sari; Bima Prana Chitra; Zuindra (Melati Institute, 2022)
This study aims to analyze the moral values that can be found in the Sad Girls Novel by Lang Leav which are the values of friendship, social behavior, responsibility, and maturity. Moral values are related to human behavior, in terms of what is considered good and bad. The values of friendship are mutual understanding between individuals, understanding everything that is liked, hated, needed. While social behavior leads to the formation of a good personality. Responsibility instead is a moral which describes a person's ability to show quality personal in their work, and maturity is an important form of moral intelligence which is the mental capacity to determine how universal human principles are. The research method used is qualitative method by choosing the dialogues that contain moral values, and the description is written using the concept of literary representation with a dynamic structuralism to propose the idea of moral values in the chosen dialogue. The result of this research shows moral characters portrayed in the novel by Audrey consistently indicated how she was being a good friend, involving in various social situations, being a responsible and mature individual with the people around her, and the main characters’ behaviors are giving the readers dialogue and actions that showed their interests and personality which brought the 4 mentioned moral values.